The research poster and how it consolidates and communicates key concepts of a research inquiry - McAuley, Mike (2019)
This article discusses a joint project between the Schools of Design at the University of Newcastle in Australia and Massey University in New Zealand. It focuses on the role of the research poster as a learning tool in assisting visual communication design students in developing expertise as researchers. Students at both universities followed a similar learning structure whereby, at the end of a thirteen-week semester, they were asked to summarise their research by designing a poster which captured the key ideas and findings of each student’s project. We will put forward here the argument that this creative, kinaesthetic-making activity allowed students to develop a clear understanding of the relationship between theory and practice, something which may not have been as effectively conveyed through an exclusively written essay structure. We also discuss the role creative, concept-based imagery played in enabling students to draw attention and communicate key ideas within a research investigation.